Voices off: Stanley Milgram's cyranoids in historical context. (December 2019) - Holmes, Marcia; Pick, Daniel
This article revisits a forgotten, late project by the social psychologist Stanley Milgram: the 'cyranoid' studies he conducted from 1977 to 1984. These investigations, inspired by the play Cyrano de Bergerac, explored how individuals often fail to notice when others do not speak their own thoughts, but instead relay messages from a hidden source. We situate these experiments amidst the intellectual, cultural, and political concerns of late Cold War America, and show how Milgram's studies pulled together a variety of ideas, anxieties, and interests that were prevalent at that time and have returned in new guises since. In discussing the cyranoid project's background and afterlife, we argue that its strikingly equivocal quality has lent itself to multiple reinterpretations by historians, psychologists, performers, artists, and others. Our purpose is neither to champion Milgram's work nor to amplify the critiques already made of his methods. Rather, it is to consider the uncertain, allusive, and elusive aspects of the cyranoid project, and to seek to place that project in context, whilst asking where 'context' might end. We show how the experiments' range of meanings, in different temporal registers, far exceeded the explanatory rubric that Milgram and his intellectual critics provided at that time, and ponder the risk for the historian of making anachronistic or teleological assumptions. In short, we argue, cyranoids invite our open-ended exploration of 'voices offstage' in social and psychological relations, and offer a useful tool for thinking about historical context and the nature of historical interpretations.